An application method for targeted degradation of VOCs by composite zero-valent iron materials of waste batteries

By disassembling the waste batteries and mixing them with zero-valent iron material to form an iron-based composite material and combining it with sodium carboxymethylcellulose, the problem of short life and high cost of VOCs treatment is solved, low cost and long life interception and removal of VOCs is achieved, and pollution to the ecological environment is reduced.

CN115945057BActive Publication Date: 2025-04-15SHANGHAI SECOND POLYTECHNIC UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211629522.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-19
Publication Date
2025-04-15
Estimated Expiration
2042-12-19

AI Technical Summary

Technical Problem

In the prior art, VOCs treatment methods have problems with short life and high replacement cost, and it is difficult to effectively reduce pollution to the ecological environment by treating waste batteries.

Method used

By disassembling the waste batteries, the positive electrode material is divided into mixed with zero-valent iron material to form an iron-based composite material and combined with sodium carboxymethylcellulose to form a film-like substance to retain and remove VOCs.

Benefits of technology

The low cost and long life of VOCs are achieved, and the pollution to the ecological environment is reduced, and the valuable metals are simultaneously recovered.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of waste gas purification and treatment, and provides an application of waste batteries. The application is to remove VOCs with waste batteries as raw materials, including the following steps: S1, dismantle the waste batteries and sort out the positive electrode materials; S2, add the positive electrode materials to nitric acid to dissolve, and add an appropriate amount of zero-valent iron materials; magnetic stirring, react for a period of time, centrifuge to obtain solid matter; S3, add the solid matter obtained in step S2 to a ball mill, and obtain an iron-copper composite material after ball milling for a period of time; S4, the solid matter obtained in step S3 is mixed with a sodium carboxymethyl cellulose solution, stirred evenly at a speed of 800r / min, and fully dissolved; S5, the composite material obtained in step S4 is placed in a spraying device, and the sodium carboxymethyl cellulose will form a film within 10 minutes to achieve the interception or removal of VOCs. The present invention dismantles and utilizes waste batteries, turns waste into treasure, reduces environmental pressure, and can achieve the interception and synchronous removal of VOCs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of waste gas purification and treatment, and relates to a method for utilizing a composite zero-valent iron material of waste batteries to target and degrade VOCs. Background Art

[0002] The composition and sources of volatile organic compounds (VOCs) are complex. Natural sources include volcanic eruptions, biomass burning, etc.; human sources include petrochemical processes, fossil fuel transportation and application processes. VOCs can be transferred between different phases, thus causing serious harm to the atmospheric environment and human body.

[0003] Traditional methods for VOCs treatment include condensation, absorption, combustion and adsorption. However, for different VOCs, activated carbon adsorption is currently widely used, but it has the disadvantages of short life and high replacement cost.

[0004] Waste batteries are batteries that have been used and discarded. Zinc-manganese batteries and alkaline-manganese batteries are mainly composed of heavy metals such as manganese, mercury, and zinc. Whether waste batteries are in the atmosphere or buried deep underground, their heavy metal components will overflow with seepage, causing groundwater and soil pollution. In 1998, the "National List of Hazardous Wastes" defined mercury, cadmium, zinc, lead, and chromium as hazardous wastes. In recent years, as people pay more attention to the ecological environment, how to deal with waste batteries has become an important and difficult issue. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a low-cost and long-life VOCs treatment method, by using waste materials as raw materials to prepare raw materials for volatile organic compound treatment, and to achieve the retention and removal of VOCs.

[0006] In view of the problems in the prior art, the present invention provides a method for targeted degradation of VOCs using composite zero-valent iron materials from waste batteries.

[0007] On the one hand, the present invention provides an application of waste batteries, which are used as raw materials for removing VOCs. The method first utilizes waste batteries, disassembles them, sorts out the positive electrode materials, and after acid dissolution, adds zero-valent iron materials, magnetically stirs and centrifuges to obtain solid substances. The solid substances are then mixed with micron iron powder through a ball mill to obtain an iron-based composite material. After magnetic stirring and centrifugation, the remaining supernatant from which the solid substances are removed can continue to recover valuable metals such as cobalt and lithium. Finally, an appropriate amount of sodium carboxymethyl cellulose is added and mixed with the iron-based composite material to fully dissolve. Sodium carboxymethyl cellulose will form a film in a short time, which can achieve the retention or removal of VOCs.

[0008] Preferably, by using waste batteries as raw materials, the interception and removal of VOCs can be achieved simultaneously.

[0009] On the other hand, the present invention provides a method for targeted degradation of VOCs using a composite zero-valent iron material of waste batteries, the method comprising the following steps:

[0010] (1) Dismantle the waste battery, separate the positive electrode material, and obtain the leaching solution after acid dissolution. Preferably, the stirring conditions are: at room temperature, control the solid-liquid ratio to 1:20-30, and the time is 2 hours.

[0011] (2) Mixing the micron iron powder with the positive electrode material obtained in step (1), and mixing them thoroughly for a certain period of time under argon conditions to obtain an iron-based composite material.

[0012] (3) The composite material obtained in step (2) is mixed with the sodium carboxymethyl cellulose solution, and stirred at a speed of 800 r / min to be uniformly dissolved.

[0013] (4) The composite material obtained in step (3) is placed in a spraying device, and the sodium carboxymethyl cellulose forms a film in a short time (e.g., within 10 minutes), thereby achieving the interception and / or reduction and removal of VOCs. The source of VOCs is not limited and can be used for wastewater. Preferably, the concentration range of VOCs is 50-200 mg / m 3 .

[0014] Preferably, the acid is nitric acid with a concentration of 1.0-3.0 mol / L.

[0015] Preferably, the mixing is performed using a ball mill. The ball milling conditions are a rotation speed of 300-500 rpm and a time of 1-5 hours, such as 2-4 hours. Alternatively, the mass ratio of the micron iron powder to the acid is 1:1-3.

[0016] Preferably, in step (2), the particle size of the micron iron powder is in the range of 50-100 nm, and can form an alloy with the powder of step (1).

[0017] Preferably, in step (2), the iron-based composite material is added to 1-3 mol / L nitric acid for leaching, magnetic stirring, centrifugation and obtaining a solid material; the obtained solid material is calcined at high temperature for 2-4 hours to obtain an iron alloy material composite material. The reaction time of magnetic stirring can be 1-minute.

[0018] Preferably, the dosage of the sodium carboxymethyl cellulose is 1.0-2.0 g.

[0019] Preferably, the VOCs include but are not limited to H2S, mercaptans, trichloromethane or trichloroethylene.

[0020] Preferably, the spray equipment includes handheld portable and overhead spray type spray equipment; the handheld portable spray equipment is used for open unorganized VOCs treatment, or the overhead spray type spray equipment is used for centralized treatment after efficient capture.

[0021] The present invention disassembles and utilizes waste batteries, turning waste into treasure and reducing the pollution and damage caused by waste batteries to the ecological environment. The positive electrode of the waste battery is disassembled and mixed with micro-iron particles, which are then combined with carboxymethyl cellulose sodium to intercept VOCs and prevent them from further diffusion. The iron in the composite material has strong reducing properties and can reduce and remove VOCs. In addition, the iron forms an alloy with the powder made from the treated positive electrode of the waste battery, which slows down the agglomeration of the iron material on the one hand and strengthens the reducing performance of the iron on the other hand, ultimately achieving the interception and synchronous removal of VOCs. DETAILED DESCRIPTION

[0022] The present invention discloses a method for using waste batteries, which uses waste battery composite zero-valent iron materials to target and degrade VOCs. The method comprises the following steps: first, using waste batteries, disassembling and sorting out positive electrode materials, and subjecting the dissolution to acid treatment to obtain a leachate; then, the leachate is mixed with micron iron powder in a ball mill to obtain an iron-based composite material; finally, the iron-based composite material is fully dissolved in an appropriate amount of sodium carboxymethyl cellulose solution to obtain a final material. This method utilizes sodium carboxymethyl cellulose to form a film in a short time, thereby achieving the interception of VOCs and preventing them from further diffusion, and the iron in the composite material has a strong reduction property, which can reduce and remove VOCs, thereby achieving the interception and synchronous removal of VOCs.

[0023] The technical solution will be clearly and completely described below through the embodiments of the present application. Obviously, the described embodiments are only part of the preferred embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0024] Comparative Example

[0025] (1) Mix micron iron powder and sodium carboxymethyl cellulose (1.0 g), stir evenly at a speed of 800 r / min until fully dissolved; set aside;

[0026] (2) placing the composite material obtained in step (1) in a top spraying device, conducting a hydrogen sulfide interception reaction experiment using a simulated upflow reactor, setting an air distribution plate to facilitate uniform distribution of hydrogen sulfide in the pipeline, and spreading quartz sand material on the air distribution plate to facilitate film formation of the composite material.

[0027] Example 1

[0028] (1) The discarded batteries are disassembled, the positive electrode materials are separated, and after heat treatment, a powdery substance of 20-50 μm is obtained.

[0029] (2) After the powdery substance obtained in step (1) is dissolved in acid, a zero-valent iron material is added, magnetic stirring is performed, the reaction is performed for 2 minutes, centrifugation is performed to obtain an iron-copper alloy, and ball milling is performed for 2 hours.

[0030] (3) The composite material obtained in step (2) was mixed with sodium carboxymethyl cellulose (1.0 g), and stirred at a speed of 800 r / min until fully dissolved; and set aside.

[0031] (4) placing the composite material obtained in step (3) in a top spraying device, and conducting a hydrogen sulfide interception reaction experiment using a simulated upflow reactor, setting an air distribution plate to facilitate the uniform distribution of hydrogen sulfide in the pipeline, and spreading quartz sand material on the air distribution plate to facilitate film formation of the composite material.

[0032] The H2S concentrations of the experimental group 1 and the control group after the reaction were tested using a handheld pump-type hydrogen sulfide detector. The results showed that the mass concentration of chloroform in the experimental group 1 was reduced by 56% compared with that in the control group.

[0033] Example 2

[0034] (1) The discarded batteries are disassembled, the positive electrode materials are separated, and after heat treatment, a powdery substance of 20-50 μm is obtained.

[0035] (2) After the powdery substance obtained in step (1) is dissolved in acid, a zero-valent iron material is added, magnetic stirring is performed, the reaction is performed for 2 minutes, centrifugation is performed to obtain an iron-copper alloy, and ball milling is performed for 3 hours.

[0036] (3) The composite material obtained in step (2) was mixed with sodium carboxymethyl cellulose (2.0 g), and stirred at a speed of 800 r / min until fully dissolved; and the mixture was set aside.

[0037] (4) placing the composite material obtained in step (3) in a top spraying device, and conducting a hydrogen sulfide interception reaction experiment using a simulated upflow reactor, setting an air distribution plate to facilitate the uniform distribution of hydrogen sulfide in the pipeline, and spreading quartz sand material on the air distribution plate to facilitate film formation of the composite material.

[0038] The H2S concentrations of the experimental group 1 and the control group after the reaction were tested using a handheld pump-type hydrogen sulfide detector. The results showed that the mass concentration of chloroform in the experimental group 1 was reduced by 68% compared with that in the control group.

[0039] Example 3

[0040] (1) The discarded batteries are disassembled, the positive electrode materials are separated, and after heat treatment, a powdery substance of 20-50 μm is obtained.

[0041] (2) After the powdery substance obtained in step (1) is dissolved in acid, a zero-valent iron material is added, magnetic stirring is performed, the reaction is performed for 2 minutes, centrifugation is performed to obtain an iron-copper alloy, and ball milling is performed for 4 hours.

[0042] (3) The composite material obtained in step (2) was mixed with sodium carboxymethyl cellulose (2.0 g), and stirred at a speed of 800 r / min until fully dissolved; and the mixture was set aside.

[0043] (4) placing the composite material obtained in step (3) in a top spray device, and conducting a chloroform interception reaction experiment using a simulated upflow reactor, setting an air distribution plate to facilitate uniform distribution of hydrogen sulfide in the pipeline, and spreading quartz sand material on the air distribution plate to facilitate film formation of the composite material.

[0044] The concentration of chloroform in the experimental group 1 after the reaction was completed was detected by gas chromatography. The results showed that the mass concentration of chloroform in the experimental group 1 was reduced by 87% compared with that in the control group.

[0045] The above-described embodiments are only specific implementation methods of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be thought of by any technician familiar with the art within the technical scope disclosed in the present application without creative work should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims in the present application.

Claims

1. Application of waste batteries, characterized in that: Use waste batteries as raw materials to remove VOCs; The application comprises the following steps: S1. Disassemble the discarded batteries and sort out the positive electrode materials; S2. adding the positive electrode material into nitric acid for leaching, adding zero-valent iron material, magnetic stirring, and centrifuging to obtain a solid substance; S3. ball-milling the solid material obtained in step S2 to obtain an iron-copper composite material; recovering valuable metals from the remaining supernatant; S4. The iron-copper composite material obtained in step S3 was mixed with the sodium carboxymethyl cellulose solution and stirred at a speed of 800 r / min to fully dissolve; S5. The composite material obtained in step S4 is placed in a spraying device, and the sodium carboxymethyl cellulose forms a film in a short time to achieve the interception and / or reduction and removal of VOCs.

2. The use according to claim 1, characterized in that The interception and removal of VOCs and the recovery of valuable metals are achieved simultaneously; the valuable metals include but are not limited to cobalt and lithium.

3. A method for targeted degradation of VOCs using waste battery composite zero-valent iron materials, characterized in that: The method comprises the following steps: (1) Dismantling the discarded batteries and sorting out the positive electrode materials; (2) adding the positive electrode material obtained in step (1) into nitric acid for dissolution, adding micron iron powder, magnetically stirring, centrifuging and obtaining a solid substance; ball milling the obtained solid substance to obtain an iron-copper alloy; (3) mixing the iron-copper alloy obtained in step (2) with the sodium carboxymethyl cellulose solution, stirring evenly at a speed of 800 r / min to fully dissolve; (4) The iron-copper alloy obtained in step (3) is placed in a spraying device, and the sodium carboxymethyl cellulose will form a film in a short time to achieve the interception and / or reduction and removal of VOCs.

4. The method according to claim 3, characterized in that The nitric acid concentration is 1.0-3.0 mol / L.

5. The method according to claim 3, characterized in that In step (2), the positive electrode material is added to 1-3 mol / L nitric acid for leaching to obtain a mixed acid, micron iron powder is added, magnetic stirring is performed, and centrifugation is performed to obtain a solid substance; the obtained solid substance is calcined at a high temperature for 2-4 hours, and the calcination temperature is 600-800° C. to obtain an iron-copper alloy.

6. The method according to claim 5, characterized in that The ball milling conditions are a rotation speed of 300-500 rpm and a time of 1-5 h; or a mass ratio of micron iron powder to mixed acid of (1-3):

1.

7. The method according to claim 3, characterized in that The particle size range of the micron iron powder is 50-100 nm; or The film-forming time of sodium carboxymethyl cellulose is no more than 10 minutes.

8. The method according to claim 3, characterized in that The dosage of the sodium carboxymethyl cellulose is 1.0-2.0 g.

9. The method according to claim 3, characterized in that The VOCs include but are not limited to halogenated hydrocarbon VOCs.

10. The method according to any one of claims 3 to 9, characterized in that The spray equipment includes handheld portable and overhead spray type spray equipment; Hand-held portable spray equipment is used for open unorganized VOCs treatment, or overhead spray equipment is used for centralized treatment after efficient capture.

Citation Information

Patent Citations

  • Method for preventing impurity metal from being separated out in process of recycling negative electrode of waste lithium battery

    CN112768798A

  • Volatile organic waste gas enrichment purification and ironmaking coupling system

    CN216321101U